Awareness of breast cancer in high-risk women in Yogyakarta - Caroline, Cindy; Haryani, Haryani; Aulawi, Khudazi (BKM Public Health and Community Medicine, 2021)
Background: Breast cancer is the leading cause of death and the most frequently diagnosed in women worldwide. A person who has a mother, sister, or daughter with breast cancer has a twofold risk of developing breast cancer. Public and individual awareness play an essential role in health promotion, early diagnosis, and treatment of breast cancer. Objective: To describe breast cancer awareness among high-risk women in Yogyakarta. Methods: This survey asked 100 breast cancer high-risk women to answer 36-item Breast Cancer Awareness Scale in Indonesian (BCAS-I) questionnaire, from November 2019 to January 2020. Results: The average age of the respondents in this study was 31.38 years (SD = 13.016). Most respondents are high school graduates, are married, do not work, have no income, and have health insurance. Only 56% of respondents have a high level of breast cancer awareness. 62% of respondents in this study know risk factors, and 53% of respondents have high signs of symptoms. And 52% of respondents have low barriers to breast cancer screening. However, respondents who have attitudes towards breast cancer prevention and health behaviors related to breast cancer awareness are still low, 62% and 54%, respectively. Most high-risk women who experience low breast cancer awareness are in the elderly age group (65 years and over), have higher education (high school and college), have no income, and do not work but have health insurance. Conclusion: Most respondents have a high knowledge of risk factors and signs and symptoms and low barriers to breast cancer screening. However, breast cancer prevention attitudes and health behaviors related to breast cancer awareness are still low.